Degree of Discordance Between FIB-4 and Transient Elastography: An Application of Current Guidelines on General Population Cohort - Chang, Madeleine; Chang, Devon; Kodali, Sudha; Harrison, Stephen A; Ghobrial, Mark; Alkhouri, Naim; Noureddin, Mazen (Clinical gastroenterology and hepatology, 2024)
In the American Gastroenterological Association/American Association for the Study of Liver Diseases (AGA/AASLD) Clinical Care Pathway, Fibrosis-4 index (FIB-4) is used to stratify patients at risk for metabolic dysfunction-associated steatotic liver disease (MASLD) as low-, indeterminate-, or high-risk for developing advanced liver fibrosis. We assessed the performance of FIB-4 in a general population. Using the 2017 to 2020 National Health and Nutrition Examination Surveys dataset, we selected subjects ≥18 years who had FibroScan data. We followed AGA/AASLD guidelines to identify subjects with characteristics that place them at risk for MASLD-associated liver fibrosis. Other causes of liver disease were excluded. Our final cohort had 3741 subjects. We then categorized these subjects based on recommended FIB-4 cutoffs. FibroScan liver stiffness measurement (LSM) served as the outcome measurement. Among the 2776 subjects (74.2%) classified as low risk by FIB-4, 277 subjects (10%) were not classified at low risk by LSM, and 75 subjects (2.7%) were classified as high risk by LSM. Among the 86 subjects classified as high risk by FIB-4, 68 subjects (79.1%) were not at high risk by LSM, and 54 subjects (62.8%) were at low risk by LSM. Subjects misclassified by FIB-4 as low risk were older; had a higher body mass index, waist circumference, glycohemoglobin A1c level, alanine transaminase, aspartate transaminase, diastolic blood pressure, controlled attenuation parameter score, white blood cell count, alkaline phosphatase, and fasting glucose level; but had lower high-density lipoprotein, and albumin level (all P < .05). Misclassified subjects were also more likely to have prediabetes/diabetes. Using FIB-4 in the AGA/AASLD guidelines to risk-stratify subjects at risk for MASLD-associated fibrosis results in many subjects being misclassified into the low- and high-risk categories. Therefore, it may be worthwhile considering caution in interpretation and/or alternative strategies.